A Numerical Investigation on Scaling Rolling Friction Effects in Shaking Table Model Tests. (3rd October 2019) - Li, Shanshan; Wei, Biao; Zuo, Chengjun; He, Xuhui
Abstract : Friction action is a damping mechanism used in civil structures. It often works together with traditional viscous damping. The rolling friction action is nonlinear, and its scaling process in shaking table model tests is suspect, especially in cases of working in combination with traditional viscous dampers. To solve the problem, a numerical model of simplified viscous damper-Coulomb friction base isolation system was scaled. The comparison between the scaled and the prototype model results showed two important factors that influence the scaling of rolling friction action. One factor is the unscaled gravity acceleration, which results in an adverse friction force and seismic responses of scaled models. These adverse seismic responses can be improved by changing the friction coefficient to correct for the abovementioned adverse friction force in the dynamic equation. Another factor is the friction variation in space, causing adverse scaled seismic responses. These adverse seismic responses can be improved by moving the variable friction positions along the scaled size of contact surface. The influence of the above two factors can be weakened by increasing the traditional viscous damping component and the earthquake intensity.